REAL OPTIONS ANALYSIS – ASSESSMENT METHOD OF INVESTMENT PROJECTS IN GREEN ENERGY - MAFTEI DANIEL (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2014)
This article highlights the importance of real options as a evaluation method of investment in green energy. Article consider several theoretical and practical approaches, the analysis based on real options by many authors who have theorized and used this method. Each approach provides a operationalisation through a steps series of specific evaluation. This paper highlights the different views: academics, financiers, managers and facilitates the access to an accurate evaluation decisions of projects.